Raymond Roussel and the Republic of Dreams - Ford, Mark (Cornell University Press, 2019)
Raymond Roussel, one of the most outlandishly compelling literary figures of modern times, died in mysterious circumstances at the age of fifty-six in 1933. The story Mark Ford tells about Roussel's life and work is at once captivating, heartbreaking, and almost beyond belief. Could even Proust or Nabokov have invented a character as strange and memorable as the exquisite dandy and graphomaniac this book brings to life?Roussel's poetry, novels, and plays influenced the work of many well-known writers and artists: Jean Cocteau found in him "genius in its pure state," while Salvador Dalí, who died with a copy of Roussel's Impressions d'Afrique on his bedside table, believed him to be one of France's greatest writers ever. Edmond Rostand, Marcel Duchamp, André Breton, Michel Foucault, and Alain Robbe-Grillet all testified to the power of his unique imagination.By any standards, Roussel led an extraordinary life. Tremendously wealthy, he took two world tours during which he hardly left his hotel rooms. He never wore his clothes more than twice, and generally avoided conversation because he dreaded that it might turn morbid. Ford, himself a poet, traces the evolution of Roussel's bizarre compositional methods and describes the idiosyncrasies of a life structured as obsessively as Roussel structured his writing
Description based on online resource; title from PDF title page (publisher's Web site, viewed 20. Jun 2019)
Keywords: Roussel, Raymond -- 1877-1933; BIOGRAPHY & AUTOBIOGRAPHY / Literary